Governance of Hindu Early Childhood Education Curriculum After Covid-19 Pandemic in Mataram City - Ardika Yasa, I Made; Lasmawan, I Wayan; Putu Suharta, I Gusti (Jurnal Syntax Admiration, 2023)
The research uses a critical Qualitative Research method that explores the Implementation of Hindu-nuanced Early Childhood Education Curriculum Management in the city of Mataram and the Contribution of Government Policy to Post-Covid-19 Pandemic Curriculum Governance for Hindu-nuanced ECCE in Mataram City and the Implications of Curriculum Policy Implementation on the readiness of Hindu-nuanced ECCE facilities and infrastructure in Mataram City. Based on the results of surveys and research conducted, it is known that PAUD or kindergarten teachers in Mataram City who are Hindus find it difficult to adjust and understand the new curriculum due to differences in situations and conditions of supporting infrastructure for learning activities in schools and the diversity of perspectives on understanding the curriculum so that it is necessary to get socialization, workshops or training related to strengthening the Hindu-based curriculum in order to be able to develop a Hindu-based curriculum well. Thus, it is very necessary for the participation of the Government, PG-ECCE Lecturers, and Stakeholders in supporting curriculum development and motivating ECCE Teachers to further improve their quality and quality in line with the potential and negative impacts of the Covid-19 pandemic so that in the future they are always ready to face a change or when a similar outbreak occurs in the future.